Educational Perspectives on Mediality and Subjectivation Discourse, Power and Analysis - Bettinger, Patrick (Palgrave Studies in Educational Media, 2022)
This open access book examines the complex relationship between education, media and power. Exploring the entanglement of education media and power structures, the contributions use various examples and case studies to demonstrate how subjectivation processes and digital structures interact with one another. The book asks which modes of subjectivation can be identified with current media cultures, how subjects deal with the challenges and potential of digitality, and how coping and empowerment strategies are developed. By addressing theoretical as well as empirical evidence, the chapters illuminate these connections and the subsequent significance for media education more widely.